Diagnostic approach to neurotransmitter monoamine disorders: experience from clinical, biochemical, and genetic profiles. Issue 1 (18th September 2017) - Kuster, Alice; Arnoux, Jean‐Baptiste; Barth, Magalie; Lamireau, Delphine; Houcinat, Nada; Goizet, Cyril; Doray, Bérénice; Gobin, Stéphanie; Schiff, Manuel; Cano, Aline; Amsallem, Daniel; Barnerias, Christine; et al.
Abstract: Background and aim: To improve the diagnostic work‐up of patients with diverse neurological diseases, we have elaborated specific clinical and CSF neurotransmitter patterns. Methods: Neurotransmitter determinations in CSF from 1200 patients revealed abnormal values in 228 (19%) cases. In 54/228 (24%) patients, a final diagnosis was identified. Results: We have reported primary (30/54, 56%) and secondary (24/54, 44%) monoamine neurotransmitter disorders. For primary deficiencies, the most frequently mutated gene was DDC ( n = 9), and the others included PAH with neuropsychiatric features ( n = 4), PTS ( n = 5), QDPR ( n = 3), SR ( n = 1), and TH ( n = 1). We have also identified mutations in SLC6A3, FOXG1 ( n = 1 of each), MTHFR ( n = 3), FOLR1, and MTHFD ( n = 1 of each), for dopamine transporter, neuronal development, and folate metabolism disorders, respectively. For secondary deficiencies, we have identified POLG ( n = 3), ACSF3 ( n = 1), NFU1, and SDHD ( n = 1 of each), playing a role in mitochondrial function. Other mutated genes included: ADAR, RNASEH2B, RNASET2, SLC7A2‐IT1 A/B lncRNA, and EXOSC3 involved in nuclear and cytoplasmic metabolism; RanBP2 and CASK implicated in post‐traductional and scaffolding modifications ; SLC6A19 regulating amino acid transport; MTM1, KCNQ2 ( n = 2), and ATP1A3 playing a role in nerve cell electrophysiological state. Chromosome abnormalities, del(8)(p23)/dup(12) (p23) ( n = 1), del(6)(q21) ( n = 1), dup(17)(p13.3) ( n = 1), and non‐genetic etiologies ( n = 3) were also identified. Conclusion: We have classified the final 54 diagnoses in 11 distinctive biochemical profiles and described them through 20 clinical features. To identify the specific molecular cause of abnormal NT profiles, (targeted) genomics might be used, to improve diagnosis and allow early treatment of complex and rare neurological genetic diseases.